Mapping risk factors for cumulative life course impairment in patients with chronic skin diseases – a systematic review. (25th June 2021) - von Stülpnagel, C.C.; Augustin, M.; Düpmann, L.; da Silva, N.; Sommer, R.
Abstract: Patients with chronic skin diseases suffer from physical and psychosocial impairments which can lead to a cumulative life‐long burden. Therefore, the concept of cumulative life course impairment (CLCI) was introduced, referring to the non‐reversible damage due to the persistent life‐long burden. This systematic review (PROSPERO registry number: CRD42020179141) aimed at mapping the risk factors and the associated burden over time in patients with psoriasis, atopic dermatitis (AD) and hidradenitis suppurativa (HS). Three electronic databases were searched (date of the last search: December 2019). Studies with a longitudinal study design that assessed the association between a risk factor and the associated burden over time in patients with psoriasis, AD and HS were included. Quality assessment of the included studies was done using Critical Appraisal Skills Programme (CASP) checklists. In total, 40 publications reflecting 25 different studies were included: nine studies addressed patients with psoriasis, 13 patients with AD, two studies included patients with HS and one study enrolled patients with psoriasis and AD, respectively. Twenty‐two potential risk factors with underlying evidence were found in this review. These risk factors include mainly sociodemographic (such as age or gender) and clinical (such as disease severity or comorbidities) variables. Disease severity and comorbidities were the most often studied risk factors, while only a few studies evaluated psychosocial risk factors over time. Patients with chronic skin diseases are at high risk to develop a life‐long negative impact from the disease. However, there is a lack of data that evaluates the psychosocial burden and its influence on the patients' life course over time. The risk factors found in this review help to identify patients at risk, to treat them adequately and, ultimately, to prevent CLCI. These results can be the basis to develop a highly needed tool to assess the risk for CLCI in the future.